Exploring the Impact of Social Media on Mental Health: A Comparison Between Young Students and the Elderly in Pakistan (Medical Forum Monthly, 2024)
Objective: The basic aim of the study is to find the impact of social media on mental health a comparison between young students and the elderly in Pakistan.Study Design: mixed-method approach studyPlace and Duration of Study: This study was conducted at the Institute of Psychiatry, Benazir Bhutto hospital Rawalpindi from November 2022 to October 2023.Methods: This mixed-method approach study was conducted in Institute of Psychiatry, Benazir Bhutto hospital Rawalpindi from Nov 2022 to October 2023 to investigate the divergent impacts of social media on the mental health of young students and elderly individuals. Data were collected through a combination of surveys, questionnaires, interviews, and focus groups. Structured surveys and questionnaires assessed social media usage patterns, mental health indicators, self-esteem, social comparison tendencies, and perceived benefits or drawbacks of social media.Results: Data was collected from 300 participants of different age groups. Young students predominantly comprised undergraduate students (70%) engaged in full-time education, with a gender distribution of 45% male, 54% female, and a minimal representation of other genders (1%). For young students, social connectivity displayed a positive correlation (0.5) with reduced feelings of loneliness, while entertainment and recreation exhibited a moderate positive correlation (0.3) with improved mood. Additionally, information seeking did not exhibit significant correlations with stress or anxiety (0.2), whereas self-expression showed a mild correlation (0.2) with enhanced self-esteem.Conclusion: It is concluded that social media usage manifests distinct impacts on the mental health of young students and elderly individuals, delineating divergent patterns in stress, anxiety, and feelings of isolation.